Analisis Kesalahan Penggunaan Partikel Penanda Nominatif -i/ga dan Akusatif eul/reul dalam Karangan Pendek Mahasiswa - Airulsari, Arisha; Hanani, Iva (East Asian Review, 2024)
This article describes the types and frequencies of errors in the use of the nominative case marker 이/가 (i/ga) and the accusative case marker 을/를 (eul/reul) in short essays written by second-semester students of the Korean Language and Culture Department, Universitas Gadjah Mada. This study analyzed 93 short essays written on the midterm and final exams for the Korean Reading and Writing II course in the 2021/2022 academic year. This research uses both qualitative and quantitative methods. The errors were classified based on the particle usage error classification theory proposed by Jo Cheol Hyeon (2002). The research results showed that there were 66 data in total found in the students' short essays. Of the total 36 data of nominative case marker이/가(i/ga) errors, there were 22 data (61.11%) of substitution errors, 13 data (36.11%) of deletion errors, and 1 data (2.78%) of form error. Then, of the total 31 data of accusative case marker을/를 (eul/reul) errors, there were 20 data (66.67%) of substitution errors and 10 data (33.33%) of deletion errors. One of the factors that is thought to contribute to the occurrence of errors in the use of nominative case marker이/가 (i/ga) and accusative case marker을/를 (eul/reul) is inadequate knowledge of the word class of a Korean sentence predicate. This causes learners to be unable to correctly determine the arguments that function as subject and object in a sentence.